Dispositional factors in cognitive emotional response among employees of telecommunication companies: implication for counseling. (2008)
The study examined dispositional factors in cognitive emotional response among employees in telecommunication companies in Nigeria. This was necessitated by the desire to understand the coping strategies of employees and the factors that influence their choices which have not been considered in performance improvement studies. of the telecommunication industry in Nigeria. A sample size of253 was selected through accidental sampling technique from two telecommunication companies in Lagos. Instruments used for data collection are: cognitive emotional response questionnaire (CERQ), self-esteem and the proactive attitude scales. Pearson correlation and t-test were used to test the hypotheses generated. Findings revealed significant relationship among proactive attitude, emotion focused coping strategy and problem focused coping strategy. Self-esteem significantly influenced the choice of emotional- focused coping strategy. Age of employees was also found to be a factor in the type of coping strategy adopted. Based on these, it implies that adjustment of employees largely depend on personal factors they bring to the workplace. Therefore, it was recommended that there is the need to incorporate intervention services in the organizations to offer employees opportunities for result-oriented counseling that would guide them in choosing coping strategies when faced with stressful experiences at work